Updating Dewey's Transactional Theory of Action in Connection with Evolutionary Theory - Kivinen Osmo; Piiroinen Tero (Palgrave Macmillan, 2022)
John Dewey’s ‘habit’-centered, transactional theory of action gets rid of the Cartesian mind–world dualism by replacing ‘mind-first’ explanations of action with ‘action-first’ explanations of the mind. Dewey embraced Darwinian thinking, and built his theory of action in an evolutionary framework. Of course, he could not have foreseen all the developments in theory and research on human evolution that have unfolded since his time; evolutionary theory and understanding have been elaborated, for example, with the idea of co-evolutionary niche construction. This chapter outlines an update of Dewey’s transactional theory of action, drawing on, among others, Daniel Dennett’s, Andy Clark’s, and Kim Sterelny’s works, and some recent developments in theories and research on the brain, mind, and the evolution of human culture. A sort of ‘four E’—extensive, enactive, embodied, and embedded—notion of the mind is considered, as well as other recent ideas and conceptual tools, such as (socio-cultural) niche construction, the Sterelnian apprentice learning setup, the Clarkian conception of predictive processing as a central function of the brain, affordances of action, and the Dennettian understanding that in evolution, competence comes before comprehension, and the latter could arise only with culture.
John Dewey and the Notion of Trans-action: A Sociological Reply on Rethinking Relations and Social Processes